2022
DOI: 10.1530/etj-22-0055
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of thyroid function assessment in infants born to mothers with thyroid dysfunction during pregnancy

Abstract: Introduction: Maternal thyroid disease is considered as a risk factor for abnormal thyroid function at birth as well as for long-term morbidity in offspring. The potential harmful effects on the neonate had led to the clinical practice of thyroid function assessment in infants born to mothers with thyroid disease during pregnancy. We evaluated the usefulness of routine thyroid function tests for every newborn of a mother with thyroid dysfunction. Methods: Data were collected retrospectively from the medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Among the studies included in this review, four have detected cases of CH with additional thyroid function tests that were missed during the initial screening programme. 20,[25][26][27] The largest of these was published in 2022 by Ben-Zeev et al and comprised 701 infants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the studies included in this review, four have detected cases of CH with additional thyroid function tests that were missed during the initial screening programme. 20,[25][26][27] The largest of these was published in 2022 by Ben-Zeev et al and comprised 701 infants.…”
Section: Discussionmentioning
confidence: 99%
“…The third had a sibling with CH. 26 The authors suggested that thyroid function testing for all newborns of mothers with thyroid dysfunction is rather redundant. However, it may be useful in cases of a positive history of CH in siblings, along with a more careful follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrolyte abnormalities are prevalent and must be assessed to rule out hyponatremia from excessive water consumption, hypokalemia from excessive purging, or hypocalcaemia and hypomagnesaemia from incorrect laxative usage. Thyroid function, as well as plasma ferritin, folate, and vitamin B12, should be evaluated (Ben-Zeev et al, 2022;D'Aurizio et al, 2022;Fang et al, 2022).…”
Section: Inspectionmentioning
confidence: 99%